2019
DOI: 10.1590/2177-6709.24.3.44.e1-9.onl
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors related to malocclusion, normative and perceived orthodontic treatment need among children and adolescents in Bangladesh

Abstract: Objective: The purpose of the present study was to assess the prevalence of normative and perceived orthodontic treatment need in schoolchildren and adolescents, related risk factors, and children/parent’s aesthetic perception, compared to orthodontist’s opinion, in Dhaka city, Bangladesh. Methods: A random sample of 800 schoolchildren aging 11-15 years was selected from different schools in the city of Dhaka, Bangladesh. The Dental Health Component (DHC) and Aesthetic Component (AC) of the Index of Orthodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
1
7
1
9
Order By: Relevance
“…40 Besides, lower results were reported in Brazil (20.0%) 41 and Bangladesh (24.7%). 21 The difference between our study and others might be due to the ethnicity difference and the use of variable criteria for the classification of the malocclusion.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…40 Besides, lower results were reported in Brazil (20.0%) 41 and Bangladesh (24.7%). 21 The difference between our study and others might be due to the ethnicity difference and the use of variable criteria for the classification of the malocclusion.…”
Section: Discussioncontrasting
confidence: 56%
“…[15][16][17][18][19] In Africa, the prevalence of class-I malocclusion was 89%. 20 The prevalence of malocclusion was 24.7% in Malaysia, 21 and 23.7% in Ethiopia. 22 An institutionbased cross-sectional study in children in Southwest Ethiopia found a high prevalence of Overjet (30.8%) and Crowding (23.3%).…”
mentioning
confidence: 99%
“…The demographic data from the current study were in agreement with a study conducted in Singapore, where 55.9% of participants were female (Tan et al, 2019). In Dhaka, Bangladesh, the same trend of gender distribution can also be observed, where about 50.4% of the total number of participants were female (Sultana and Hossain, 2019).…”
Section: Discussionmentioning
confidence: 57%
“…This results is similar to a study conducted in Yemeni (Al-Zubair, 2014). However, recent studies show that most common malocclusion in adolescents is class2 malocclusion (Gelgör et al, 2007;Bilgic et al, 2015;Sultana and Hossain, 2019).…”
Section: Resultsmentioning
confidence: 99%